Rediscovery of a species considered to be extinct in the Pollino massif (Calabria, Italy): Erebia gorge (Hübner, [1804]) (Lepidoptera: Nymphalidae) - Piazzini, Sandro; Favilli, Leonardo (Fragmenta entomologica, 2020)
After about 40 years, the presence of Erebia gorge (Hübner, [1804]) has been reconfirmed in the Pollino massif (Calabria, Italy). In July 2019, two specimens (1 ♂ and 1 ♀) were captured in the zone of Monte Pollino cliffs on the east face of the massif at a height of 1990 m. Given the isolation of the population at the southernmost limit of the species’ range, and the fact that this population is seriously threatened by global climate change, it would be of great value to conduct an exhaustive study of the distribution of the species throughout Pollino and of the genetic characteristics of this local population that could differ substantially from other Italian and European populations.